The Influence of the Commercial Banking System on the Development of the National Economy - Jočienė, Aldona; Staškevičius, Juozapas Audvydas (Ekonomika, 1997)
Commercial banks play a strategic role in the functioning of economics. They are the main source for of money supply. Banks regulate the country's payment system and credit economy, and they provide different services related to securities, investments, etc.In the article the significance of commercial banks on the country's economy is defined by characterising their core functions: money creation, payments, settlements, deposit accumulation, crediting, storage of valuables, financing of foreign trade, and trust operations.